AGING-DEPENDENT CHANGES IN ADIPOSE PRECURSORS. (20th December 2022) - Sul, Hei Sook; Lin, Frances
Abstract: Adipose tissue mass and adiposity change throughout the lifespan. During aging, while visceral adipose tissue (VAT) tends to increase, peripheral subcutaneous adipose tissue (SAT) decreases significantly. Unlike VAT, which is linked to metabolic diseases, including type 2 diabetes, SAT has beneficial effects. However, the molecular details behind the aging-associated loss of SAT remain unclear. Here, by comparing scRNA-seq of total stromal vascular cells of SAT from young and aging mice, we identify an aging-dependent regulatory cell (ARC) population that emerges only in SAT of aged mice and humans. ARCs express adipose progenitor markers but lack adipogenic capacity; they secrete high levels of pro-inflammatory chemokines, including Ccl6, to inhibit proliferation and differentiation of neighboring adipose precursors. We also found Pu.1 to be a driving factor for ARC development. We identify an ARC population and its capacity to inhibit differentiation of neighboring adipose precursors, correlating with aging-associated loss of SAT.